(3GdLhgQI GdefjaI aj TQM hUjI GdEeGe CHj MfjaIs - (3efdG MSjf Hf EScfOQ GdMfajs; (3GdGeGe CHh MfjaIs
(3ChdgG (B:s
(3hHYO aEfi GSJNQJ Gddg JYGdi ai hVY TQM eNJUQ Ydi cJGH GdhUjI GdefShHI Edi GdEeGe GdCYXe CHj MfjaI Gd s
(3BNQgG (B:s
(3aGFOI jQhi Cf GdedGFcI bGd jG QH dh Ef GdSehGJ hGdCQV Mjf CeQJgeG YUGc eG cfJ UGfYkG HgeG hGdMeO ddg Ydi GdJeGe hGdceGd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs